Adolescent Alcohol Use Patterns From 25 European Countries. (October 2015) - Bräker, Astrid-Britta; Göbel, Kristin; Scheithauer, Herbert; Soellner, Renate
This study's purpose is to describe European adolescents' alcohol use patterns by grouping adolescents regarding their current alcohol use by cluster analysis (CA). Discriminant and latent profile analyses (LPA) evaluate and validate the solution that will be described further by ANOVAs. From 25 European countries, 57, 771 students (49.4% male, 13.87 years) are grouped using hierarchical and k -means clustering. Alcohol use is measured by frequency of drinking occasions during the previous month and number of beverages consumed on the last drinking occasion. CA suggests four drinking patterns: mild (73.6%), episodic (20.0%), frequent (3.8%), and heavy episodic use (2.5%). Discriminant analysis attests a classification reliability of 94%, and confirmatory LPA replicates the cluster solution with a satisfying model fit. Three of the found patterns fulfill criteria for heavy drinking and underline the importance of individualized indicated prevention by promoting responsible use.